The Step-Count Accuracy of Activity Monitors on Land and in the Water: Revisited. Issue 2 (May 2021) - Stevens, Sandra; Michaels, Natalie Norman; Noven, Marnie Vanden; Caputo, Jennifer; Johnson, Samantha L.
Abstract : Background: Activity monitors are used by people from all walks of life in the United States and elsewhere. Various companies boast their monitors can be used both on land and in the water, but the accuracy of these monitors when determining step count is unknown. This study is based on a pilot study published in 2019 by the same authors. Methods: Six popular water-resistant activity monitors were tested on 27 participants. Participants walked on a land treadmill for 3 minutes at a self-selected, comfortable walking speed while wearing 2 land/water activity monitors (one on each wrist) that were randomized across participants. This was repeated in the water on a HydroTrack (by HydroWorx) underwater treadmill. All walks were filmed so the actual step count could be determined for comparison with the counts from the monitors. Results: The accuracy of each monitor for step count on land and in the water was determined by comparing the monitor's calculation with the actual step count using correlation, mean step difference, Cohen's d calculation, paired t test for significance, and intraclass correlation. Relevance: This study provides further information regarding the accuracy of activity monitors in assessing step count on land and in the water. Continued research is recommended using a larger number of monitors, with individuals of varying ages and conditions.